2010
DOI: 10.1002/mus.21784
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing spinal muscular atrophy with electrical impedance myography

Abstract: Electrical impedance myography (EIM) is a non-invasive, painless technique for the evaluation of neuromuscular disease, and here we evaluate its potential application in spinal muscular atrophy (SMA). Twenty-one SMA patients and 18 healthy children underwent EIM of biceps brachii and tibialis anterior using a commercially available impedance device. Hand-held dynamometry and ultrasound assessment of subcutaneous fat thickness were also performed. All EIM parameters differed significantly between both SMA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
101
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 18 publications
(21 reference statements)
3
101
0
1
Order By: Relevance
“…Of all the predetermined EIM measures studied, only the high‐frequency reactance slope distinguished SMA from healthy children; many of the standard measures that have shown differences in older children27, 35 did not do so in this group of infants. Moreover, EIM measures only correlated with motor function in the healthy children.…”
Section: Discussionmentioning
confidence: 86%
“…Of all the predetermined EIM measures studied, only the high‐frequency reactance slope distinguished SMA from healthy children; many of the standard measures that have shown differences in older children27, 35 did not do so in this group of infants. Moreover, EIM measures only correlated with motor function in the healthy children.…”
Section: Discussionmentioning
confidence: 86%
“…Another American research group 13 showed that 21 patients with types II and III SMA have higher levels of adiposity than subjects without the disease, considering either the thickness of subcutaneous fat tissue or the use of multifrequency bioelectric impedance. In agreement with this study, subcutaneous fat evaluated by a skinfold thickness caliper in 25 SMA patients (type II: 15; type III: 10 patients) was higher (type II: 12.5 mm; type III: 8.82 mm) than that of individuals without the disease (average of 5.37 mm) in the United States 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the methods used to evaluate body composition in children, bioelectrical impedance stands out as a noninvasive and painless method, which has already been adopted by other authors while evaluating SMA patients 13 , or children and adolescents without the disease [14][15][16] . Body girth measurements are frequently used in clinical practice 17,18 due to their practical character and low price.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we take this approach for the first time in neuromuscular disease, by combining features from 2 unrelated technologies, quantitative muscle ultrasound (QMU) 10 -16 and electrical impedance myography (EIM) 17,18 to determine whether SVM algorithms can more accurately classify normal muscles and those affected by type 2 and type 3 spinal muscular atrophy (SMA) than either method alone.…”
Section: Discussionmentioning
confidence: 99%